Identification of Herbs and Shrubs in the Lemor Botanical Garden Forest Area, Suela District, East Lombok Regency - Balqis, Yasina; Mertha, I Gde; Raksun, Ahmad (Jurnal Biologi Tropis, 2025)
The diversity of plants in a conservation area or forest is important data that can be used as a recommendation in efforts to maintain ecosystem balance, especially in herbaceous and shrubby plants that are rarely studied so that access to plant data is very limited. For this reason, this study aims to identify herbaceous and shrubby plants in the Lemor Botanical Garden Forest Area, East Lombok. This study is a qualitative descriptive study with cruise methods by tracing the exploration route. The findings show that in the area, 21 species from 19 families of herbaceous and shrubby plants were identified. In detail, 13 species from 11 families of herbaceous plants were found with the majority of species having upright, creeping, and epiphytic habitus and 8 species from 8 families of shrubby plants were found, the majority of which had upright habitus. The existence of various herbaceous and shrubby plants plays an important role in maintaining ecosystem stability so that stricter conservation efforts are needed by related institutions to maintain the diversity of existing species.